MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA SMP 1 LEMBANG MELALUI PENDEKATAN KONTEKSTUAL PADA MATERI FUNGSI DAN PERSAMAAN GARIS LURUS - Junaidah (JURNAL EKSPERIMENTAL : Media Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2017)
This study aims to examine the achievement and improvement of students' mathematical communication skills of SMP 1 Lembang on the material of straight line functions and equations, as well as examine the interaction between learning and KAM on improving students' mathematical communication skills. This research is a quasi-experimental research with Non-equivalent Control Group Design. The population in this study were all eighth grade students in one of the junior high schools in Lembang. The research sample was determined using purposive sampling. The sample consisted of two classes, the experimental class which received learning with a contextual approach, and the control class which received expository learning. The instrument used is in the form of students' communication ability test questions. The findings of this study are: (1) The achievement and improvement of mathematical communication skills of students who receive learning using a contextual approach is better than students who receive ordinary learning both as a whole and in KAM. (2) There is no interaction between learning and KAM (high, medium, low) on the achievement of students' mathematical communication skills